Simulasi Numerik Kendali Kapal Cepat Tak Berawak Dua Propeller Tanpa Rudder - Muhammad Arifudin Lukmana; Qisthi Alhazmi Hidayatur-Rohman; Fahrudin Fahrudin; Noverdo Saputra (Politeknik Negeri Jakarta, 2021)
This paper discusses the simulation of automation control and hull manufacturing on a fast boat. This high-speed boat that will be carried out for fish mapping. This study uses a numerical simulation to predict its motion. The experiment was carried out 3 times in forward motion, and 3 times in turn motion. The ship’s time and movement in ideal conditions will be recorded for each experiment. With the PID value for forward overshoot with values such as: 8.94%, 30.86%, and 40.60%, while turning overshoot is obtained, among others: 25.77%, 49.82%, and 61.15% Then the advanced settling time obtained includes: 0.91 seconds, 3.84 seconds, and 5.31 seconds. The settling time for turns is: 1,022 seconds, 0.85 seconds, and 0.84 seconds These values are obtained from the simulation graph of the three-dof formulas for surge, sway, yaw.